Kepemimpinan Dalam Manajemen Pendidikan Islam - Shukatin; Zulqarnain (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The doctrine of Islamic leadership has long emerged even further before other themes. The doctrine of leadership in Islam is closely related to the purpose of the creation and descent of humans into this world. As creatures who inhabit the earth, humans are burdened with the mandate of istikhlaf. According to A. Hasim, the mandate of istikhlaf (rule of the earth) is not merely a kingdom, power, authority and government, but it is all with the provision that it must be used for prosperity and development in order to prove what God has outlined for humans so that they can walk on it. to the level of perfection. Management of Islamic education is a process of managing Islamic educational institutions in an Islamic way by dealing with learning resources and other related matters to achieve the goals of Islamic education effectively and efficiently. The role and actions of Islamic education leadership in various Islamic education management systems are actually a form of actualization of the values attached to them and become a personality. Therefore, the quality of Islamic education is also measured by the quality of its leaders. Educational leadership is the process of influencing and guiding a leader to educators and education staff to carry out educational and research tasks using existing educational facilities, both individually and in groups, so that educational goals are achieved effectively and efficiently